Fungal extracts stimulate solitary chemosensory cell expansion in noninvasive fungal rhinosinusitis. Issue 7 (20th March 2019) - Patel, Neil N.; Triantafillou, Vasiliki; Maina, Ivy W.; Workman, Alan D.; Tong, Charles C. L.; Kuan, Edward C.; Papagiannopoulos, Peter; Bosso, John V.; Adappa, Nithin D.; Palmer, James N.; Kohanski, Michael A.; Herbert, De'Broski R.; et al.
Abstract : Background: Solitary chemosensory cells (SCCs) are rare epithelial cells enriched in nasal polyps and are the primary source of interleukin‐25 (IL‐25), an innate cytokine eliciting T‐helper 2 (Th2) immune response. Although it is proposed that SCCs are stimulated by antigens released by upper airway pathogens, the exogenous triggers of human SCCs remain elusive. We studied patients with noninvasive fungal rhinosinusitis to determine whether extracts of Aspergillus fumigatus and Alternaria alternata stimulate SCC proliferation as an early event in type 2 inflammation. Methods: Multicolor flow cytometry, immunofluorescence, and enzyme‐linked immunoassay were used to interrogate mucosa from patients with mycetomas and allergic fungal rhinosinusitis (AFRS) for SCCs and IL‐25. Primary sinonasal epithelial cells from AFRS patients and noninflamed inferior turbinates were stimulated with fungal extracts for 72 hours, and SCC population frequency as well as mitotic activity were quantified using flow cytometry. Results: SCCs producing IL‐25 are enriched in inflamed mucosa compared with intrapatient noninflamed control tissue (38.6% vs 6.5%, p = 0.029). In cultured sinonasal epithelial cells from AFRS nasal polyps, Aspergillus fumigatus and Alternaria alternata stimulated higher SCC frequency compared with controls (27.4% vs 10.6%, p = 0.002; 18.1% vs 10.6%, p = 0.046), which led to increased IL‐25 secretion in culture media (75.5 vs 3.3 pg/mL, p < 0.001; 32.3 vs 3.3 pg/mL, p = 0.007). Ki‐67 expression was higher in SCCs grown in fungal stimulation conditions compared with controls. Conclusion: Although fungal antigens are known to potentiate immune response through innate cytokines, including IL‐25, the early expansion of SCCs in the presence of fungus has not been described. This early event in the pathogenesis of noninvasive fungal rhinosinusitis may represent a target for intervention.